Menumbuhkan Rasa Cinta Lingkungan Melalui Pembelajaran Bahasa Inggris Berbasis Potensi Alam Di Desa Persiapan Empol - Mertha, I Wayan; Setiawan, Heru; Ilmi, Muhamad Yazid Mizanul; Jamí’’yyah, Shafro’Khuluq; Putri, Hermaya Sura; Aini, Jannatul; Delphi, Syakila Gita; Utami, Ulya Febria; Ropidah, Risky Riyyatul; Niarni, Baiq Gina Amalia; Alhafizin, M.; Astuti, Julya (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Desa Persiapan Empol has natural potential in the form of mangrove ecosystems, fish ponds, and salt, which can be integrated into environmental-based learning. To optimize learning and the understanding of children about local potential while also improving their English proficiency, a contextual and interactive educational approach is needed. This program aims to improve the English competency of children aged 7-13 years and foster an environmental love through learning based on the village’s natural potential. The activities involve socialization and practical methods conducted in the Bertong, Madak, and Empol hamlets. The results of the activities show an improvement in the children's English skills, particularly in speaking and descriptive writing, as well as an increase in their awareness of the importance of environmental preservation. This program also introduces the village's natural resources as valuable assets that need to be preserved, helping children understand the ecological and economic value of local resources